The ethics of animal labor : a collaborative utopia - Porcher, Jocelyne (Palgrave Macmillan, 2017)
This work argues for a moral consideration of animal work relations. Paying special attention to the livestock industry, the author challenges the zootechnical denigration of animals for increased productivity awhile championing the collaborative nature of work. For Porcher, work is not merely a means to production but a means of living together unity. This unique reconsideration of work envisions animals as co-laborers with humans, rather than overwrought tools for exploitative, and often lethal, employment. Readers will learn about the disjunction between those focused on productivity and profit and those who favor a more ethical work environment for animals. Porcher's text also engages environmental and political debates concerning animal-human relations.
Keywords: Working animals -- Moral and ethical aspects.; elektronické knihy; electronic books